Integrative Approaches to Enhancing Primary School Students’ Economic and Environmental Literacy - Sulaymanovna, Elibayeva Lola (Researchparks Publishing, 2026)
This article explores integrative pedagogical approaches aimed at developing economic, linguistic, and environmental literacy among primary school students. The study emphasizes the importance of organizing homework as a form of independent work that promotes active learning, observation, and creativity rather than rote memorization. It highlights the need for integration between reading literacy, native language, and mathematics lessons to strengthen students’ vocabulary, independent thinking, and problem-solving skills. A set of economic concepts suitable for primary school grades is proposed to systematically develop children’s financial awareness within the curriculum. Moreover, the paper underlines the educational value of nature-based activities, excursions, and didactic games in fostering ecological and moral values. Through the use of interdisciplinary lessons, tests, and interactive teaching methods, the article demonstrates how integration across subjects can enhance both academic performance and personal development in the early years of schooling.